Local Economic Adaptation Strategies Towards the Impact of Global Warming in Eastern Indonesia - Kurniawan, Panji Rizki; Safitri, Reni Silvia Yuli (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Global warming has had a significant impact on the local economy in Eastern Indonesia, a region encompassing East Nusa Tenggara, Maluku, North Maluku, Papua, and West Papua. This study aims to identify the specific impacts of global warming on key economic sectors and analyze adaptation strategies developed by local communities based on the framework of adaptive capacity theory. Using a qualitative literature study method with a systematic analysis of scientific publications, government reports, and policy documents over the past four years, this study found that global warming has had a serious impact on three sectors supporting the local economy: fisheries have experienced a 20-30 percent decline in catch due to coral bleaching and shifts in fish migration; agriculture has been disrupted by changing rainfall patterns, leading to uncertain planting seasons and increased pest infestations; and marine tourism has declined due to coastal ecosystem degradation. Communities have responded to these impacts through five main adaptation strategies: livelihood diversification, utilization of local knowledge and technological innovation, strengthening institutions and social networks, increasing access to finance and insurance, and developing value chains and market access. However, the effectiveness of these adaptation strategies remains constrained by a limited economic asset base, institutional weaknesses, knowledge gaps, limited innovation capacity, and weak coordination among stakeholders. This study concludes that increasing local economic resilience requires a holistic approach that simultaneously strengthens all five dimensions of adaptive capacity through infrastructure investment, institutional strengthening, human resource capacity building, and responsive policies, with active collaboration between the government, local communities, the private sector, and non-governmental organizations.